Studi Deskriptif Fenomena Breadcrumbing sebagai Kekerasan Berbasis Gender Online (KBGO) pada Generasi Z Pengguna Aplikasi Telegram - Anggi Oktavianda; Aflah Zakinov Irta (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the breadcrumbing experience of female adolescent victims of online gender-based violence (GBV) through Telegram's Anonymous Chat feature, identify the underlying factors, and explain the resulting impacts. The study used a qualitative approach with a descriptive design to explore the subjects' experiences in depth. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results show that breadcrumbing occurs as a gradual process of manipulation, beginning with the need for affection and the search for emotional validation, then developing into ambiguous virtual closeness, inconsistent attention, sexual grooming, and forms of digital control and threats. These findings indicate that breadcrumbing is not only an uncertain virtual relationship but also a pattern of relational manipulation that has the potential to become a gateway to GBV. Therefore, this study emphasizes the importance of strengthening digital literacy and healthy relationship education as an effort to prevent and protect adolescents in the digital space.